Why do (or do not) banks share customer information? A comparison of mature private credit markets and markets in transition - Iván Major (Hungarian Academy of Sciences, Institute of Economics, 2006)
Credit bureaus administering information sharing among lenders about customers reduce information asymmetry and should be key to modern credit markets. In contrast to former studies, we show that willingness to share information depends more on institutions and market concentration than on demand or other market characteristics such as, regional diversity or local monopolies. We show using infinite period models with strategic behavior that lenders' interest to share information depends on market concentration and the type of information sharing arrangement. Sharing bad information only is the dominant strategy if banks think long-term. If banks are myopic no information sharing may occur.
Keywords: D23; D81; D82; D92; G21; 330; Organisational Behaviour; Transaction Costs; Criteria for Decision-Making under Risk and Uncertainty; Asymmetric and Private Information; Intertemporal Firm Choice and Growth; Investment; or Financing; Banks; Other Depository Institutions; Mortgages; Bank; Kreditmarkt; Kreditkarte; Kreditsicherung; Wissenstransfer; Theorie